Policing, punishment and comparative penality. (16th September 2022) - Newburn, Tim; Jones, Trevor
Abstract: Apparently growing punitiveness in many countries toward the end of the twentieth century prompted considerable criminological activity which focused on attempting to understand trends and contrasts in systems and patterns of punishment. Although to date this literature has tended to treat policing and punishment as being largely separate spheres of activity this paper advances two reasons for paying greater attention to policing in this context. First, and briefly, to reflect the fact that the police are the 'gatekeepers' to the penal system, and therefore in some senses inseparable from other penal practices. Second, and more centrally, that in various forms policing both involves, and is often experienced as, punishment. Attempts to understand the nature of and differences between penal states will be enhanced by the inclusion of policing within its ambit.